EFFECTS OF THAI MUSLIM PURCHASING BEHAVIOR TOWARDS FOREIGN BRANDS USAGE OF THE HALAL SIGN OF IMPORTED GOODS IN THAILAND - Ahadi, Navidreza; Taghipour, Amirhossein; Deebhijarn, Samart; Sornsaruht, Puris (PEOPLE: International Journal of Social Sciences, 2015)
This research explores the effects and importance of the halal sign on foreign imported products among Thai Muslims as well as Thai non-Muslims. It covers a brief background of halal products in Thai society and organizations that control and promote the halal concept in Thailand. In addition, the study looks at the role that halal plays in Muslim culture, purchasing behavior, and corporate brand image identity, the paper investigates the concept of halal from a religious point of view based on the Hadith and the Quran. It is argued in the paper that the halal sign is one of the most important symbols that encourage Muslim purchasing intention and it has some influence on other religions as well.